It is the expression 3 + 2a.
(a - 6)(2a + 3)
19-3 in a verbal expression = 16
That verbal expression would read: 3(x+y)^2 + 5(2x -y) ^2 means 'squared' in the above example.
To simplify the expression 2a - 3 + 4b - 2a - b - 3 + 5, we first combine like terms. Combining the terms with 'a', we have 2a - 2a = 0. Combining the terms with 'b', we have 4b - b = 3b. Combining the constants, we have -3 - 3 + 5 = -1. Therefore, the simplified expression is 3b - 1.
3b -1
(2a - 3)(3a - 4)
9a +8 -2a -3 -5a = 2a +5
2
I guess you mean: 2a^2+6a Well in this case you take 2a out of the bracket and then you're left with a+3 inside. 2a(a+3a)
+3
(3 - i)(3 + i)